SHATTERED FRONTS: THE EXPLOSIVE INTERPLAY OF GENDER AND WARFARE IN THE 20TH CENTURY - Liliana Akhmedova (Journal Of Social And Political Science, 2026)
This аrticle takes a closer look at how gender and warfare impacted each other across 20th century. Wars did not just change borders-they shook up the lives and roles of men and women in ways that still echo today. With examples from World War I, World War II, the Cold War, and struggles for independence, I show how war pushed people into new roles: women took on factory and military jobs, while societies sometimes doubled down on traditional gender rules once the fighting stopped. By digging into diaries, interviews, and a range of historical sources, I try to show both sides of the story-how war could open doors for women and challenge old ideas, but also how those changes did not always last. Understanding this back-and-forth helps us see why gender and war are still linked today, and why the lessons from that era matter for anyone thinking about equality, identity, or policy now.